Respostas

2013-01-12T00:52:55-02:00

a)  (x-1)/3 - (x-2)/2    2

 mmc  de 3 e 2  = 6, portanto

 

2(x-1) - 3(x-2)   2

2x - 2 - 3x + 6   12

-x +4   12

-x   8

x ≥ -8

{x pertence a R| x  -8}

 

b) 2(3 - x)/5 + x/2  ≥ 1/4 + 2(x - 1)/3

 mmc de 5,2,4,3 = 60, portanto

 

12.2(3-x) + 30.x   15 + 20.2(x-1)

72 - 24x + 30x   15 + 40x - 40

-24x + 30x - 40x   15 -72 -40

-34x   -97

  x 97/34

   {x pertence a R| x  97/34}

 

c)3x - 1/4 - x - 3/2 ≥ x+ 7/4 

mmc de 2,4 = 4, portanto

 

4.3x  - 1 - 4x - 2.3  4x + 7

12x - 4x -4x - 6  7 + 1 + 6

12x  14

 x  14/12

 x  7/6

 {x pertence a R| x  7/6}